If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 = 15h Solving 45 = 15h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-15h' to each side of the equation. 45 + -15h = 15h + -15h Combine like terms: 15h + -15h = 0 45 + -15h = 0 Add '-45' to each side of the equation. 45 + -45 + -15h = 0 + -45 Combine like terms: 45 + -45 = 0 0 + -15h = 0 + -45 -15h = 0 + -45 Combine like terms: 0 + -45 = -45 -15h = -45 Divide each side by '-15'. h = 3 Simplifying h = 3
| 6X+13= | | 9=b(b-8) | | y+2=0.1y | | 3x^2-x^2-8x-5=0 | | 2(4x+2)-10=74 | | 12a+3+18+9a= | | 1/3(6x-9)=2x-3 | | 86-3X=42X+16 | | 4.5x+(-5)=17 | | 10(1-2(.5))=-5(2(.5)-1) | | 9-10X=53-24X | | p-5.16=15.48 | | 12(2-x)=4-6(x+2) | | 93+-84= | | 10(1-2(1.5))=-5(2(1.5)-1) | | x-4y=48 | | 3+4y=4a+7 | | 15r+9=96 | | 6p^2+21p= | | 93=-84 | | 7x+3=8x-2 | | r(s+4)+9(s+4)= | | 5z^3+14z^2-24z=0 | | r^4=625 | | 4x-15=4x | | 4x^4-121=0 | | 3(1+6b)+3(6-3b)=21 | | 77-5x=7-9x | | 19x=11x | | 5+6x=25x | | 11x+50=6x+25 | | 2x^3+3x^2-72x-108=0 |